Ответы и объяснения

2012-09-05T14:19:16+00:00

|\frac{x}{x+1}|=2x+6

x/(x+1)=2x+6                               x/(x+1)=-2x-6

x=(2x+6)(x+1)                              x=(-2x-6)(x+1)

x=2x^2 +2x +6x +6                       x=-2x^2 -2x -6x -6

2x^2-7x +6=0                               2x^2 +9x +6=0

D=49-4*6*2=49-48=1                     D=81-4*6*2=81-48=33

x1=(7+1)/4=2                                x1=(-9+sqrt(33))/4

x2=(7-1)/4=1,5                              x2=(-9-sqrt(33))/4

Ответ: 2; 1,5; (-9+sqrt(33))/4 ; (-9-sqrt(33))/4.

Необходимо все проверить!

sqrt-корень